Family law - Standley, Kate (The Macmillan Press, 1993)
'Family Law' provides an account of a rapidly developing subject. The sixth edition includes up-to-date coverage of the latest major developments in family law such as Domestic Violence, Crime and Victims Act 2004, and new features such as Key Words in each chapter to make it even more student-friendly